A manufacturing process of a silent motor rotor core stack and curing
Patent Information
- Application Number
- CN202611330215.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]为了解决现有转子铁芯叠压固化工艺,易造成铁芯的成型精度不足的问题,本申请提供一种静音电机转子铁芯叠压固化制造工艺
1、由于本申请采用梯度升温分级固化处理包括依次进行的至少三个温度台阶,粘接剂的交联反应被分散至多个温度区间内分步进行,避免了单一高温条件下一次性交联引发的收缩应力集中;由于各温度台阶之间程序升温且压力同步切换,各温度台阶的温度值依次升高且分别对应不同的叠压压力,使压力随固化反应进程同步调整,将固化收缩转化为正向压紧力;由于叠压工装在各温度台阶之间保持对铁芯的轴向加压状态,避免了铁芯在温度切换过程中发生回弹或错位;由于固化完成后在保持叠压压力的条件下进行程序降温,使热收缩应力在受控条件下逐步释放,因此,获得了提高铁芯成型精度的效果。
Smart Images

Figure CN122993368A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of motor manufacturing technology, and more specifically, it relates to a manufacturing process for the stacking and curing of a rotor core for a silent motor. Background Technology
[0002] The stacking of stator and rotor cores plays a crucial role in the overall performance of motors during manufacturing. The quality of the core stacking directly affects whether the motor's noise and other performance indicators meet relevant regulations, and whether the motor can be shipped as qualified. The rotor core is typically composed of multiple electrical steel laminations stacked axially and then fixed together. With the development of motors towards higher precision and lower noise, higher requirements are placed on the stacking accuracy, structural compactness, and coaxiality of the rotor core.
[0003] In existing rotor core lamination and curing processes, curing is usually completed in one go under a single high-temperature condition or in stages under limited stepped heating conditions. The lamination pressure is either applied once before curing and not adjusted afterward, or it is adjusted intermittently between heating stages by removing the tooling. This results in the curing shrinkage caused by the cross-linking reaction of the adhesive not being compensated for in real time by the lamination pressure. The curing shrinkage is converted into harmful residual stress inside the core instead of positive clamping force that helps improve the lamination coefficient, resulting in insufficient core forming accuracy. Summary of the Invention
[0004] To address the problem of insufficient forming accuracy of rotor cores caused by existing rotor core lamination and curing processes, this application provides a manufacturing process for the lamination and curing of rotor cores for silent motors.
[0005] This application provides a silent motor rotor core lamination and curing manufacturing process, which adopts the following technical solution: A manufacturing process for the laminated and cured rotor core of a silent motor includes the following steps: S1. The rotor laminations coated with adhesive are stacked in a stacking fixture, and an initial pre-pressure is applied to the rotor laminations for pre-pressure positioning. S2. The stacking fixture and the iron core loaded therein are subjected to gradient heating and graded curing treatment. The gradient heating and graded curing treatment includes at least three temperature steps performed in sequence. The temperature steps are programmed to increase in temperature and the pressure is switched synchronously. The stacking fixture maintains an axial pressure on the iron core between each temperature step. Each temperature step corresponds to a stacking pressure, and the temperature value of each temperature step increases sequentially. S3. Perform programmed cooling on the cured iron core while maintaining the stacking pressure; S4. After cooling to the set temperature, release the pressure and remove the cured rotor core from the stacking fixture.
[0006] By adopting the above technical solution, the cross-linking reaction of the adhesive is dispersed into multiple temperature ranges and carried out step by step due to the gradient temperature-level curing process, which includes at least three temperature steps performed sequentially. This avoids the concentration of shrinkage stress caused by one-time cross-linking under a single high temperature condition. Because the temperature is programmed and the pressure is switched synchronously between each temperature step, the temperature value of each step increases sequentially and corresponds to different stacking pressures, allowing the pressure to be adjusted synchronously with the curing reaction process, converting curing shrinkage into positive clamping force. Since the stacking fixture maintains axial pressure on the core between each temperature step, it prevents the core from springing back or misaligning during temperature switching. After curing, the temperature is programmed to decrease while maintaining the stacking pressure, allowing the thermal shrinkage stress to be released gradually under controlled conditions. Therefore, the core forming accuracy is improved, solving the problem of insufficient core forming accuracy that is common in existing rotor core stacking and curing processes.
[0007] Preferably, in step S1, the adhesive is a latent epoxy resin adhesive system, comprising, by weight: 90-110 parts epoxy resin, 5-15 parts latent curing agent, and 1-5 parts latent curing accelerator; the adhesive is applied to the surface of the rotor lamination by spraying or roller coating, and the coating thickness is 3-10 μm.
[0008] By adopting the above technical solution, a latent epoxy resin adhesive system is used. This system has sufficient storage stability at room temperature and gradually releases curing activity after heating, allowing the adhesive to have differentiated reaction rates at different temperature steps, which is compatible with the gradient heating and staged curing process. At the same time, the coating thickness is controlled within an appropriate range, so that the adhesive forms a continuous and uniform film on the lamination surface. This ensures the integrity of the bonding layer between the laminations and avoids the problem of excessive coating thickness leading to increased curing shrinkage or insufficient coating thickness leading to insufficient bonding strength. This ensures the bonding quality and structural compactness of the iron core.
[0009] Preferably, in step S1, the initial pre-pressure is 1-3 MPa, and the initial pre-pressure is maintained for 5-15 minutes.
[0010] By adopting the above technical solution, an initial pre-pressure is applied and maintained for a certain period of time after the stacking is completed, so that each lamination is initially positioned and in close contact before the curing reaction starts. This eliminates the loose gaps between laminations that may exist during the stacking process. At the same time, the adhesive coated on the lamination surface is fully spread and wetted under pressure, providing an initial state with accurate lamination position and good interface contact for subsequent gradient temperature graded curing treatment, thereby ensuring the stacking coefficient and structural uniformity of the iron core.
[0011] Preferably, in step S2, the gradient temperature-level curing process includes a first temperature step, a second temperature step, and a third temperature step performed sequentially.
[0012] By adopting the above technical solution, the gradient temperature-level curing process uses a first temperature step, a second temperature step, and a third temperature step in sequence. The first temperature step corresponds to the pre-curing stage and is used to initiate the initial cross-linking reaction of the adhesive. The second temperature step corresponds to the main curing stage and is used to realize the main cross-linking reaction of the adhesive. The third temperature step corresponds to the post-curing stage and is used to complete the deep cross-linking of the adhesive. The three temperature steps each have a specific curing function and are connected in sequence, so that the cross-linking reaction of the adhesive is carried out in stages in different temperature ranges, thereby ensuring the forming accuracy of the iron core.
[0013] Preferably, the temperature of the first temperature step is 60-80℃, the pressure is 3-6MPa, and the holding time is 20-40 minutes; the temperature of the second temperature step is 90-110℃, the pressure is 6-10MPa, and the holding time is 40-80 minutes; the temperature of the third temperature step is 120-140℃, the pressure is 3-5MPa, and the holding time is 20-40 minutes.
[0014] By adopting the above technical solution, the temperature, pressure and holding time of the first, second and third temperature steps are set in coordination to enable the adhesive to achieve preliminary cross-linking, full cross-linking and deep cross-linking in each step. Under the pressure coordination, the curing shrinkage is released step by step in the three steps and converted into positive compressive force, thereby ensuring the stacking coefficient and structural compactness of the iron core.
[0015] Preferably, in step S2, the heating rate between each temperature step is 1 to 3 °C / min; the pressure of the second temperature step is greater than the pressure of the first temperature step, and the pressure of the second temperature step is greater than the pressure of the third temperature step.
[0016] By adopting the above technical solution, the temperature is programmed to rise at a suitable rate between each temperature step, so that the core temperature transitions smoothly between each step, avoiding temperature shock and thermal stress mutation caused by rapid heating; at the same time, the pressure at each temperature step shows a change law of first increasing and then decreasing with the curing process. In the main curing stage, higher pressure is used to compensate for the cross-linking shrinkage of the adhesive, and in the post-curing stage, appropriate pressure is used to release residual stress, thereby ensuring the axial dimensional accuracy and coaxiality of the core.
[0017] Preferably, in step S3, the cooling rate of the programmed cooling is 1-2℃ / min, reducing the iron core from the final temperature of the gradient heating and graded solidification process to no higher than 60℃; the stacking pressure corresponding to the third temperature step is maintained during the programmed cooling process.
[0018] By adopting the above technical solution, the iron core is cooled down from the final temperature of the gradient heating and staged solidification process to no higher than the set temperature at an appropriate cooling rate. During the cooling process, the stacking pressure is maintained, so that the iron core is continuously constrained by pressure during the cooling stage. The thermal shrinkage stress is gradually released under controlled conditions rather than developing freely in an unconstrained state. This avoids thermal stress concentration and uneven deformation caused by excessively fast cooling rate or lack of pressure, thereby ensuring the dimensional stability of the iron core after cooling.
[0019] Preferably, in step S4, the set temperature is 60°C.
[0020] By adopting the above technical solution, the set temperature for depressurization and removal is limited to a temperature where the adhesive has been completely cured and has sufficient mechanical strength. After the iron core is removed from the tooling constraint, it no longer undergoes significant deformation. At the same time, this temperature level is much lower than the heat distortion temperature of the adhesive. The iron core has good dimensional stability at this temperature, which not only ensures the integrity of the curing effect, but also ensures the safety and convenience of the removal operation.
[0021] Preferably, in step S4, after removing the cured rotor core, the process further includes shot peening the outer periphery of the rotor core and removing adhesive from the inner hole of the rotor core.
[0022] By adopting the above technical solution, after the rotor core is removed and cured, shot peening is performed on the outer periphery to remove any adhesive residue that may have overflowed during the curing process and improve the surface quality of the outer circle. At the same time, adhesive removal is performed on the inner hole to remove any adhesive residue on the inner hole surface, ensuring the dimensional accuracy and cleanliness of the inner hole. The shot peening of the outer periphery and the adhesive removal of the inner hole are respectively used to repair the accuracy of different parts of the core, together ensuring the installation accuracy and reliability of the core in the subsequent assembly process.
[0023] Preferably, the adhesive has a gel time of not less than 60 minutes at 60°C, a gel time of 10-30 minutes at 100°C, and a gel time of 2-10 minutes at 140°C; the holding time of the first temperature step is less than the gel time of the adhesive system at 60°C, the holding time of the second temperature step is greater than the gel time of the adhesive system at 100°C, and the holding time of the third temperature step is greater than the gel time of the adhesive system at 140°C.
[0024] By adopting the above technical solution, a corresponding relationship is established between the gel time of the adhesive at each temperature step and the heat preservation time at each step. This allows the cross-linking reaction process of the adhesive to be coordinated with the curing process of the iron core. The pre-curing stage maintains an ungelled state to allow for further adjustment of the stamping position. The main curing stage ensures that the cross-linking reaction is fully completed, and the post-curing stage ensures that sufficient cross-linking density is achieved, thereby ensuring the bonding strength and structural stability of the iron core.
[0025] In summary, this application has the following beneficial effects: 1. Because this application employs a gradient temperature-increasing, graded curing process involving at least three sequential temperature steps, the cross-linking reaction of the adhesive is dispersed across multiple temperature ranges and carried out step-by-step, avoiding the concentration of shrinkage stress caused by one-time cross-linking under a single high-temperature condition. Since the temperature is programmed and the pressure is switched synchronously between each temperature step, the temperature value of each step increases sequentially and corresponds to different stacking pressures, allowing the pressure to be adjusted synchronously with the curing reaction process, converting curing shrinkage into positive clamping force. Because the stacking fixture maintains axial pressure on the core between each temperature step, it prevents the core from springing back or misaligning during temperature switching. After curing, programmed cooling is performed while maintaining the stacking pressure, allowing the thermal shrinkage stress to be gradually released under controlled conditions. Therefore, the effect of improving the core forming accuracy is achieved.
[0026] 2. This application sets the gradient temperature-increasing graded curing process as a first temperature step, a second temperature step, and a third temperature step, so that the adhesive goes through three stages in sequence: preliminary crosslinking, main crosslinking, and deep crosslinking. In the pre-curing stage, it is kept in an ungelled state to allow for further adjustment of the lamination position. In the main curing stage, the increased pressure compensates for crosslinking shrinkage. In the post-curing stage, the reduced pressure releases residual stress. With the synchronous switching of pressure during the programmed temperature rise between each step and the continuous axial pressure maintained by the lamination tooling, the harmful effects of curing shrinkage are eliminated step by step. The iron core is always in a controllable stress state during the curing process, thereby improving the lamination coefficient and axial dimensional accuracy of the rotor iron core.
[0027] 3. This application maintains the stacking pressure throughout the cooling process until it reaches the set temperature before depressurizing and removing the core. This allows the thermal shrinkage stress to be gradually released under controlled conditions, preventing significant deformation of the core after it is removed from the tooling constraints. After removal, the core's outer periphery is shot-peened to remove adhesive residue and improve the surface quality of the outer circle, while the inner hole is degummed to remove adhesive residue from its surface. The outer periphery shot peening and inner hole degumming are respectively used to perform precision repair on different parts of the core, jointly ensuring the installation accuracy and reliability of the core during subsequent assembly. Attached Figure Description
[0028] Figure 1This is a flowchart of a silent motor rotor core lamination and curing manufacturing process provided in this application; Figure 2 This is a diagram showing the test results of the axial dimensional tolerances provided in this application; Figure 3 This is a diagram showing the test results of radial runout provided in this application; Figure 4 This is a diagram showing the test results of the adhesive shear strength provided in this application; Figure 5 This is a diagram showing the test results of the superposition coefficient provided in this application. Detailed Implementation
[0029] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0030] Technical concept: During the stacking and curing process of rotor core, the cross-linking reaction of the adhesive is accompanied by volume shrinkage. This shrinkage will weaken the close contact between the laminations in the free state. In conventional processes, curing and stacking fail to work together effectively, and the shrinkage stress cannot be converted into beneficial clamping force. In the end, it remains in the core in the form of harmful residual stress, resulting in core warping and deformation and a decrease in coaxiality.
[0031] Based on this, this application divides the curing process into sequentially connected temperature steps. The adhesive completes the cross-linking reaction in stages at each step, and the shrinkage is released step by step. At the same time, the pressure switches synchronously with the temperature steps, so that the iron core is under a pressure state that matches the curing process at each stage, and the shrinkage stress is always converted into positive clamping force. In addition, the stacking fixture maintains a pressurized state during the step switching process, avoiding rebound and misalignment caused by pressure interruption. Combined with the pressure holding procedure and cooling after curing, the thermal stress is gradually released under controlled conditions.
[0032] Unless otherwise specified, all experimental methods used below are conventional methods. All materials, reagents, methods, and instruments used, unless otherwise specified, are conventional materials, reagents, methods, and instruments in this field, which can be obtained commercially or prepared according to literature methods by those skilled in the art.
[0033] Raw material source: epoxy resin, grade E-51, epoxy equivalent of 184-200 g / equivalent, purchased from Sinopec Baling Petrochemical Co., Ltd.
[0034] The latent curing agent is dicyandiamide, chemically known as cyanoguanidine, with the molecular formula C2H4N4, a molecular weight of 84.08, CAS Registry Number 461-58-5, industrial grade purity, and a content of not less than 99%, purchased from Ningxia Jiafeng Chemical Co., Ltd.
[0035] The latent curing accelerator is 2-methylimidazole, with the molecular formula C4H6N2, molecular weight 82.10, CAS Registry Number 693-98-1, industrial grade purity, and content not less than 99%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0036] The rotor laminations are made of 50W800 non-oriented electrical steel with a thickness of 0.5 mm, and were purchased from Baoshan Iron & Steel Co., Ltd.
[0037] To better understand the above technical solutions, the technical solutions of the present invention will be clearly and completely described below in conjunction with embodiments.
[0038] Please see the appendix Figure 1 The following is a further description with reference to the embodiments: Example 1: A manufacturing process for stacking and curing a silent motor rotor core, comprising the following steps.
[0039] Preparation of a latent epoxy resin adhesive system: 100 parts by weight of epoxy resin, 10 parts by weight of latent curing agent, and 3 parts by weight of latent curing accelerator were weighed and mixed at 60 rpm for 20 minutes at room temperature to obtain a homogeneous adhesive composition. The gel time of the adhesive at different temperatures was measured using a rotational viscometer in oscillation mode. The results were as follows: gel time of 75 minutes at 60 degrees Celsius, gel time of 20 minutes at 100 degrees Celsius, and gel time of 6 minutes at 140 degrees Celsius. The adhesive is applied evenly to the surface of the rotor laminations using a roller coating method, with the coating thickness controlled at 6.5 micrometers. The rotor laminations coated with adhesive are then stacked sequentially on the lower platen of the stacking fixture according to the designed number of laminations. Each lamination is radially positioned by the positioning guide pins on the fixture. After stacking, the upper platen is placed on the upper end face of the lamination assembly. An initial preload of 2 MPa is applied to the upper platen through the axial pressing mechanism of the stacking fixture. This pressure is maintained for 10 minutes to ensure that the lamination assembly reaches a stable stacking state within the fixture.
[0040] The stacking fixture containing the iron core is fed into the heating and curing device, and the heating system is started to perform gradient temperature rise and staged curing treatment. This gradient temperature rise and staged curing treatment is completed continuously and integrally within the stacking fixture. The switching between each pressure level is completed through the pressure adjustment mechanism of the stacking fixture itself. Throughout the curing process, the iron core remains within the stacking fixture and does not need to be removed from the fixture. The heating rate between each temperature step is 2 degrees Celsius / minute. Each temperature step corresponds to a stacking pressure, and the temperature value of each temperature step increases sequentially, with the pressure switching synchronously as the temperature increases.
[0041] The gradient temperature-increasing staged curing process involves sequentially performing three temperature steps: a first temperature step, a second temperature step, and a third temperature step. The first temperature step involves heating the core to 70 degrees Celsius while simultaneously adjusting the pressure of the lamination fixture to 4.5 MPa, and holding at this temperature and pressure for 30 minutes. The 30-minute holding time for the first temperature step is less than the 75-minute gel time of the adhesive at 60 degrees Celsius. After the first temperature step, the core temperature is increased to 100 degrees Celsius at a rate of 2 degrees Celsius / minute. When the core temperature reaches 100 degrees Celsius, the pressure of the lamination fixture is switched from 4.5 MPa to 8 MPa, initiating the second temperature step. Temperature step 1: Hold at 100°C and 8 MPa for 60 minutes; the holding time of the second temperature step (60 minutes) is 20 minutes longer than the gel time of the adhesive at 100°C; after the second temperature step is completed, the core temperature is raised to 130°C at a heating rate of 2°C / min. When the core temperature reaches 130°C, the pressure of the stacking fixture is switched from 8 MPa to 4 MPa, entering the third temperature step; third temperature step 2: Hold at 130°C and 4 MPa for 30 minutes; the holding time of the third temperature step (30 minutes) is 6 minutes longer than the gel time of the adhesive at 140°C.
[0042] After the third temperature step insulation is completed, the pressure of the stacking fixture is kept constant at 4 MPa, and the cooling program is started. The core temperature is reduced from 130 degrees Celsius to 60 degrees Celsius at a cooling rate of 1.5 degrees Celsius / minute. During the cooling process, the core remains in the stacking fixture and is continuously subjected to a pressure of 4 MPa.
[0043] After the core temperature drops to 60 degrees Celsius, the axial pressure of the stacking fixture is released, and the cured rotor core is removed from the stacking fixture. The outer periphery of the removed rotor core is shot-peened using shot peening equipment to remove adhesive residues that overflowed during the curing process. The inner hole of the rotor core is degummed to remove adhesive residues on the inner hole surface.
[0044] Example 2: This example differs from Example 1 above in that: The components of the latent epoxy resin adhesive system are: 90 parts epoxy resin, 5 parts latent curing agent, and 1 part latent curing accelerator. The adhesive has a gel time of 65 minutes at 60 degrees Celsius, 10 minutes at 100 degrees Celsius, and 2 minutes at 140 degrees Celsius. The adhesive is applied to the rotor lamination surface by spraying, with a coating thickness of 3 micrometers. The initial pre-pressure is 1 MPa, and this pressure is maintained for 5 minutes.
[0045] In the gradient temperature-stage curing process, the heating rate between each temperature step is 1 degree Celsius / minute. The first temperature step has a temperature of 60 degrees Celsius, a pressure of 3 MPa, and a holding time of 20 minutes, which is less than the gel time of the adhesive at 60 degrees Celsius (65 minutes). The second temperature step has a temperature of 90 degrees Celsius, a pressure of 6 MPa, and a holding time of 40 minutes, which is more than the gel time of the adhesive at 100 degrees Celsius (10 minutes). The third temperature step has a temperature of 120 degrees Celsius, a pressure of 3 MPa, and a holding time of 20 minutes, which is more than the gel time of the adhesive at 140 degrees Celsius (2 minutes).
[0046] The cooling rate of the programmed cooling is 1 degree Celsius per minute, reducing the iron core from 120 degrees Celsius to 60 degrees Celsius, while maintaining the pressure of the stacking fixture at 3 MPa during the cooling process.
[0047] Example 3: This example differs from Example 1 above in that: The components of the latent epoxy resin adhesive system are: 110 parts epoxy resin, 15 parts latent curing agent, and 5 parts latent curing accelerator. The adhesive has a gel time of 90 minutes at 60 degrees Celsius, 30 minutes at 100 degrees Celsius, and 10 minutes at 140 degrees Celsius. The adhesive is applied to the rotor lamination surface by spraying, with a coating thickness of 10 micrometers. The initial pre-pressure is 3 MPa, and this pressure is maintained for 15 minutes.
[0048] In the gradient temperature-stage curing process, the heating rate between each temperature step is 3 degrees Celsius / minute. The first temperature step has a temperature of 80 degrees Celsius, a pressure of 6 MPa, and a holding time of 40 minutes, which is less than the gel time of the adhesive at 60 degrees Celsius (90 minutes). The second temperature step has a temperature of 110 degrees Celsius, a pressure of 10 MPa, and a holding time of 80 minutes, which is more than the gel time of the adhesive at 100 degrees Celsius (30 minutes). The third temperature step has a temperature of 140 degrees Celsius, a pressure of 5 MPa, and a holding time of 40 minutes, which is more than the gel time of the adhesive at 140 degrees Celsius (10 minutes).
[0049] The cooling rate of the programmed cooling is 2 degrees Celsius per minute, reducing the iron core from 140 degrees Celsius to 60 degrees Celsius, while maintaining the pressure of the stacking fixture at 5 MPa during the cooling process.
[0050] Comparative Example 1: The manufacturing process of motor rotor core lamination and curing includes the following steps: Preparation of a latent epoxy resin adhesive system: Weigh 100 parts epoxy resin, 10 parts latent curing agent, and 3 parts latent curing accelerator by weight, and mix them at 60 rpm for 20 minutes at room temperature to obtain a uniform adhesive composition. Apply the adhesive evenly to the surface of the rotor laminations using a roller coating method, with the coating thickness controlled at 6.5 micrometers. Stack the rotor laminations coated with adhesive onto the lower pressure plate of the stacking fixture according to the designed number of laminations. Each lamination is radially positioned by the positioning guide posts on the fixture. After stacking, place the upper pressure plate on the upper end face of the lamination assembly, and apply an initial preload of 2 MPa to the upper pressure plate through the axial pressing mechanism of the stacking fixture. Maintain this pressure for 10 minutes to allow the lamination assembly to reach a stable stacking state within the fixture.
[0051] The stacking fixture containing the iron core is fed into the heating and curing device. The heating system is started to directly heat the iron core to 150 degrees Celsius, while the pressure of the stacking fixture is adjusted to 8 MPa. Under these temperature and pressure conditions, it is held for 120 minutes for one-time curing. After the holding period, the heating is stopped, and the stacking fixture is allowed to cool naturally to room temperature with the furnace. No additional pressure control is applied during the cooling process. After cooling to room temperature, the axial pressure of the stacking fixture is released, and the cured rotor iron core is removed from the stacking fixture.
[0052] Comparative Example 2: This comparative example differs from Example 1 above in that: In the gradient temperature-increasing staged curing process, the heating rate between each temperature step is 2 degrees Celsius / minute, proceeding sequentially through the first, second, and third temperature steps. The temperature of the first temperature step is 70 degrees Celsius, with a holding time of 30 minutes, and the pressure of the stacking fixture is 4.5 MPa. After the first temperature step is completed, the core temperature is increased to 100 degrees Celsius at a heating rate of 2 degrees Celsius / minute, entering the second temperature step. The temperature of the second temperature step is 100 degrees Celsius, with a holding time of 60 minutes. The pressure of the stacking fixture remains constant at 4.5 MPa throughout the second temperature step and does not switch synchronously with the temperature steps. After the second temperature step is completed, the core temperature is increased to 130 degrees Celsius at a heating rate of 2 degrees Celsius / minute, entering the third temperature step. The temperature of the third temperature step is 130 degrees Celsius, with a holding time of 30 minutes, and the pressure of the stacking fixture remains constant at 4.5 MPa.
[0053] Comparative Example 3: This comparative example differs from Example 1 above in that: In the gradient temperature-level curing process, the switching between pressure levels is accomplished by removing the iron core from the stacking fixture and readjusting the pressure, rather than completing the process continuously within the stacking fixture. Specifically: after the first temperature step is completed, heating is stopped, the stacking fixture is removed from the heating and curing device, the axial pressure of the fixture is released, and the pressure is readjusted to 8 MPa. Then, the stacking fixture containing the iron core is reinserted into the heating and curing device, and the temperature is raised to 100 degrees Celsius at a rate of 2 degrees Celsius / minute before the second temperature step is completed. After the second temperature step is completed, heating is stopped again, the stacking fixture is removed from the heating and curing device, the axial pressure of the fixture is released, and the pressure is readjusted to 4 MPa. Then, the stacking fixture containing the iron core is reinserted into the heating and curing device, and the temperature is raised to 130 degrees Celsius at a rate of 2 degrees Celsius / minute before the third temperature step is completed. Throughout the curing process, the iron core undergoes multiple removal and reinsertion operations from the heating device between the various temperature steps.
[0054] Comparative Example 4: This comparative example differs from Example 1 above in that: After the third temperature step insulation is completed, the temperature is not cooled down. Instead, the heating is stopped directly, the stacking fixture is removed from the heating and curing device, and it is allowed to cool naturally to 60 degrees Celsius at room temperature. During the cooling process, the pressure of the stacking fixture is not maintained. When the core temperature drops to 60 degrees Celsius, the axial pressure of the stacking fixture is released, and the cured rotor core is removed from the stacking fixture.
[0055] Comparative Example 5: This comparative example differs from Example 1 above in that: The gradient temperature-propelled staged curing process consists of two temperature steps, not three. Specifically: the first temperature step is at 70°C, with a pressure of 4.5 MPa and a holding time of 30 minutes. After the first temperature step, the core temperature is directly increased from 70°C to 130°C at a rate of 2°C / minute. When the core temperature reaches 130°C, the pressure of the stacking fixture is switched from 4.5 MPa to 4 MPa, entering the second temperature step. The second temperature step is at 130°C, with a pressure of 4 MPa and a holding time of 90 minutes. No intermediate temperature step of 100°C and 8 MPa is included in the entire gradient temperature-propelled staged curing process.
[0056] Performance testing: The rotor cores obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to the following performance tests: Axial dimensional tolerance: The axial height of the rotor core after curing is measured using a height measuring instrument. Six measuring points are evenly selected along the circumference on the upper end face of each core, and the axial height value at each point is measured. The maximum deviation between the measured height value and the theoretical design height value is calculated, and this maximum deviation is used as the evaluation value of the axial dimensional tolerance, in millimeters. Three cores are randomly selected for measurement under each process condition, and the average value is taken. Radial runout: After curing, the rotor core is mounted on a runout tester with the center hole as the reference, allowing the core to rotate freely around its axis. The dial indicator probe is placed vertically against the outer surface of the core, and the core is slowly rotated more than one revolution. The maximum change in the dial indicator reading is recorded, which is the radial runout, measured in millimeters. Radial runout is used to evaluate the coaxiality between the outer circle and the inner hole axis of the core; the smaller the value, the higher the coaxiality. Three cores are randomly selected for measurement under each process condition, and the average value is taken. Bonding shear strength: Bonded specimens were cut axially from the cured rotor core, with a bonding area of 10 mm × 10 mm. The specimens were mounted in the special shear fixture of a universal testing machine, and a tensile load was applied along the bonding surface at a loading rate of 1 mm / min. The maximum load at which the specimen failed shear along the bonding surface was recorded. The bonding shear strength was calculated using the formula τ = F / S, where τ is the bonding shear strength in MPa, F is the maximum load in Newtons, and S is the bonding area in square millimeters. Five specimens were prepared for testing under each process condition, and the average value was taken. Overlap factor: Referring to the relevant principles in GB / T 2522-2017 "Test Method for Insulation Resistance and Adhesion of Coatings on Electrical Steel Strips (Sheets)," the overlap factor of the iron core is determined by weighing. Specifically, the axial height h and radial dimension of the rotor iron core after curing are measured, and the total volume V of the iron core is calculated. The mass m of the iron core is accurately weighed, and the overlap factor is calculated according to the formula ρ. 实测 Calculate the measured density of the iron core using the formula K=ρ = m / V; 实测 / ρ 理论 Calculate the superposition factor by multiplying by 100%, where ρ 理论 The theoretical density of electrical steel is taken as 7.65 g / cm³; three iron cores are randomly selected for measurement under each process condition, and the average value is taken. Bending strength: A strip specimen measuring 10 mm × 10 mm × 50 mm was cut axially from the cured rotor core. The specimen was placed on the three-point bending fixture of a universal testing machine with a span of 40 mm. A concentrated load was applied at the mid-span of the specimen at a loading rate of 1 mm / min. The maximum load at which the specimen fractured was recorded. The bending strength was calculated using the formula σ = 3FL / (2bh²), where σ is the bending strength in MPa, F is the maximum load in Newtons, L is the span in mm, b is the specimen width in mm, and h is the specimen height in mm. Five specimens were prepared for testing under each process condition, and the average value was taken. The test results are shown in Table 1.
[0057] Table 1: Detection data for each embodiment and comparative example Example 1 0.03 0.02 5.2 98.5 85 Example 2 0.04 0.03 4.8 97.8 78 Example 3 0.03 0.02 5.0 98.2 82 Comparative Example 1 0.15 0.12 2.8 95.0 50 Comparative Example 2 0.06 0.04 3.5 96.5 62 Comparative Example 3 0.10 0.08 4.0 97.0 68 Comparative Example 4 0.12 0.06 4.2 97.5 70 Comparative Example 5 0.08 0.05 3.8 96.8 65 In conjunction with Example 1 and Comparative Example 1, and in conjunction with Table 1 and Appendix Figures 1 to 5 It can be seen that the gradient temperature staged curing treatment divides the curing process into multiple temperature steps, allowing the cross-linking reaction of the adhesive to proceed step by step within each temperature step. The curing shrinkage is dispersed and released gradually in different temperature ranges, avoiding the concentration of shrinkage stress caused by one-time curing under a single high temperature condition. In contrast, Comparative Example 1 uses a one-time heating to 150 degrees Celsius for curing. The cross-linking reaction of the adhesive occurs violently in a short time, and the shrinkage stress cannot be released in stages. The concentration of residual stress inside the iron core leads to a decrease in axial dimensional accuracy and coaxiality. At the same time, the insufficient bonding strength of the adhesive interface affects the overall structural stability of the iron core, and the stacking coefficient and bending strength both deteriorate.
[0058] In conjunction with Example 1 and Comparative Example 2, and in conjunction with Table 1 and Appendix Figures 1 to 5 It can be seen that the synchronous switching of pressure between each temperature step can ensure the densification of the iron core during the curing process; the second temperature step is the main curing stage, where the cross-linking shrinkage of the adhesive is the most severe, and applying a pressure higher than that of the first temperature step at this time can effectively compensate for the curing shrinkage; the third temperature step is the post-curing stage, and appropriately reducing the pressure can avoid excessive accumulation of residual stress; Comparative Example 2 maintains a constant pressure during each temperature step, but the pressure in the main curing stage is insufficient to compensate for the curing shrinkage, resulting in micro gaps between the laminates, and the pressure in the post-curing stage is not properly released, leading to an increase in residual stress. Therefore, the bonding shear strength, overlap factor, and flexural strength are all lower than those of Example 1.
[0059] In conjunction with Example 1 and Comparative Example 3, and in conjunction with Table 1 and Appendix Figure 2 , 3As can be seen from Figure 5, the stacking fixture can maintain the structural integrity of the iron core by maintaining axial pressure on the iron core between temperature steps. In Comparative Example 3, the iron core needs to be removed and the pressure readjusted between each temperature step before being returned. During the removal process, the iron core loses the pressure constraint of the fixture, and the tight contact state between the stacked pieces that has been initially established through pre-curing is destroyed. The gaps between the segments caused by axial springback cannot be completely eliminated by subsequent repressurization. This shows that the continuous pressure constraint of the fixture during temperature switching ensures the locking of the relative position between the stacked pieces, avoids springback and misalignment caused by pressure interruption, and thus effectively ensures the coaxiality of the iron core and the overall structural rigidity.
[0060] In conjunction with Example 1 and Comparative Example 4, and in conjunction with Table 1 and Appendix Figure 2 It can be seen that maintaining the stacking pressure during the programmed cooling process can eliminate thermal stress and ensure the dimensional accuracy of the iron core. In Comparative Example 4, the iron core was directly removed after the heat preservation was completed and allowed to cool naturally. The difference in cooling rate between the surface and the interior of the iron core resulted in uneven thermal shrinkage stress. Furthermore, the lack of tooling pressure constraint during the cooling process led to a decrease in the axial dimensional uniformity of the iron core. In Example 1, the synergistic control of programmed cooling and in-situ pressurization allowed the thermal stress to be gradually released under controllable conditions through slow cooling. At the same time, the continuous pressure constraint suppressed deformation during the cooling process, thereby ensuring the axial dimensional accuracy of the iron core.
[0061] In conjunction with Example 1 and Comparative Example 5, and in conjunction with Table 1 and Appendix Figure 3 , 4 As can be seen from Figure 5, the three temperature steps are the basis for achieving the gradual release of curing shrinkage and the matching of pressure levels. Comparative Figure 5 only has two temperature steps, directly entering the post-curing stage from the pre-curing stage. It lacks the effective compensation for the cross-linking shrinkage of the adhesive during the main curing stage. The sudden change in the reaction rate of the adhesive during rapid heating leads to uneven cross-linking network. The close contact between the laminations is destroyed under the action of shrinkage stress. The three temperature steps each have a clear functional division of labor. The first step achieves preliminary positioning and gap elimination, the second step completes shrinkage compensation and main cross-linking, and the third step achieves stress release and deep curing. The synergistic effect of each step ensures the bonding quality and structural stability of the iron core.
[0062] In conjunction with Examples 1 to 3 and Comparative Examples 1 to 5, and in conjunction with Table 1 and Appendix Figures 1 to 5It can be seen that through the coordinated operation of multiple technical features such as the setting of three temperature steps in the gradient heating and graded curing process, the sequential synchronous switching of temperature and pressure values at each temperature step, the in-situ pressurization of the stacking fixture between temperature steps, and the programmed cooling after curing, the iron core sequentially undergoes the preliminary positioning and gap elimination in the pre-curing stage, the high-pressure shrinkage compensation in the main curing stage, the residual stress release in the post-curing stage, and the smooth transition of thermal stress in the cooling stage during the curing process. There are close temporal logical connections and functional synergistic effects between each step, which together ensure the dimensional accuracy, coaxiality, bonding strength, stacking coefficient, and structural rigidity of the rotor iron core.
[0063] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A manufacturing process for stacking and curing a rotor core for a silent motor, characterized in that, Includes the following steps: S1. The rotor laminations coated with adhesive are stacked in a stacking fixture, and an initial pre-pressure is applied to the rotor laminations for pre-pressure positioning. S2. The stacking fixture and the iron core loaded therein are subjected to gradient heating and graded curing treatment. The gradient heating and graded curing treatment includes at least three temperature steps performed in sequence. The temperature steps are programmed to increase in temperature and the pressure is switched synchronously. The stacking fixture maintains an axial pressure on the iron core between each temperature step. Each temperature step corresponds to a stacking pressure, and the temperature value of each temperature step increases sequentially. S3. Perform programmed cooling on the cured iron core while maintaining the stacking pressure; S4. After cooling to the set temperature, release the pressure and remove the cured rotor core from the stacking fixture.
2. The manufacturing process for the laminated and cured rotor core of a silent motor according to claim 1, characterized in that: In step S1, the adhesive is a latent epoxy resin adhesive system, comprising, by weight: 90-110 parts epoxy resin, 5-15 parts latent curing agent, and 1-5 parts latent curing accelerator; the adhesive is applied to the surface of the rotor lamination by spraying or roller coating, and the coating thickness is 3-10 μm.
3. The manufacturing process for the laminated and cured rotor core of a silent motor according to claim 1, characterized in that: In step S1, the initial pre-pressure is 1-3 MPa, and the initial pre-pressure is maintained for 5-15 minutes.
4. The manufacturing process for the laminated and cured rotor core of a silent motor according to claim 1, characterized in that: In step S2, the gradient temperature-increasing graded curing process includes a first temperature step, a second temperature step, and a third temperature step performed sequentially.
5. The manufacturing process for the laminated and cured rotor core of a silent motor according to claim 4, characterized in that: The first temperature step has a temperature of 60–80°C, a pressure of 3–6 MPa, and a holding time of 20–40 minutes; the second temperature step has a temperature of 90–110°C, a pressure of 6–10 MPa, and a holding time of 40–80 minutes; the third temperature step has a temperature of 120–140°C, a pressure of 3–5 MPa, and a holding time of 20–40 minutes.
6. The manufacturing process for stacking and solidifying a silent motor rotor core according to claim 5, characterized in that: In step S2, the heating rate between each temperature step is 1 to 3 °C / min; the pressure of the second temperature step is greater than the pressure of the first temperature step, and the pressure of the second temperature step is greater than the pressure of the third temperature step.
7. The manufacturing process for the laminated and cured rotor core of a silent motor according to claim 1, characterized in that: In step S3, the cooling rate of the programmed cooling is 1-2℃ / min, reducing the iron core from the final temperature of the gradient heating and staged solidification process to no higher than 60℃; the stacking pressure corresponding to the third temperature step is maintained during the programmed cooling process.
8. The manufacturing process for stacking and solidifying a silent motor rotor core according to claim 7, characterized in that: In step S4, the set temperature is 60°C.
9. The manufacturing process for the laminated and cured rotor core of a silent motor according to claim 1, characterized in that: In step S4, after the rotor core has been cured, the outer periphery of the rotor core is shot peened and the inner hole of the rotor core is degummed.
10. The manufacturing process for stacking and solidifying a silent motor rotor core according to claim 5, characterized in that: The adhesive has a gel time of not less than 60 minutes at 60°C, a gel time of 10-30 minutes at 100°C, and a gel time of 2-10 minutes at 140°C; the holding time of the first temperature step is less than the gel time of the adhesive system at 60°C, the holding time of the second temperature step is greater than the gel time of the adhesive system at 100°C, and the holding time of the third temperature step is greater than the gel time of the adhesive system at 140°C.